Gender Differences in Writing Complex Sentences of CLIL-Based Bilingual Primary Students - Alfia Sari; Nunung Suryati (Universitas Lambung Mangkurat, 2025)
This present study investigated the students’ ability to produce complex sentences between male and female students who studied in a CLIL Bilingual School in Surabaya. The participants of this study were 50 primary six students. The document analysis was used to obtain data about the students’ production of complex sentences. T-unit analysis was employed to investigate the students’ proficiency in writing complex sentences. Additionally, to generate the students’ lexical richness, this study used Antconc to help generate the TTR (type-tokens ratio) on the essay. The result showed no significant differences between male and female students in their proficiency in writing complex sentences, as the p-value was higher than 0.05. It indicated that the CLIL Bilingual students’ proficiency in writing complex sentences was equal, and the input and exposure were similar. However, female students show a higher TTR and more lexical variety in producing complex sentences than male students. These findings significantly impacted understanding how gender impacts the ability to produce complex sentences when writing and using lexical variety.